Predicting the Frequency and Significance of Social Contacts Across Placements: A Bayesian Multilevel Model Analysis. (December 2022) - Jameson, J. Matt; Hicks, Tyler; Lansey, Kirsten; Kurth, Jennifer A.; Jackson, Lewis; Zagona, Alison L.; Burnette, Kristin; Agran, Marty; Shogren, Karrie; Pace, Jesse
Parents and teachers have identified the social inclusion of students with complex support needs as one of the most important components of school participation. Previous research has found that the opportunities for, and importance of, social contacts for students with complex support needs vary by educational placement. The purpose of this study was to evaluate a national sample of 92 elementary-aged students with complex support needs to determine whether placement predicts the number and importance of social contacts. We used multilevel regression analysis to measure the extent to which placement predicts the number of social contacts and teachers' ratings of importance. Students in inclusive placements had almost 50% more social contacts than students in a segregated school. Furthermore, teachers' perceptions of the social significance of the contacts experienced by students with complex support needs were notably higher in inclusive settings. Given these findings, we suggest implications for practice and future research.